Investigation of the Localized Corrosion and Passive Behavior of Type 304 Stainless Steels with 0.2–1.8 wt % B - Heon-Young Ha (Materials, 2018)
The pitting corrosion resistance and passive behavior of type 304 borated stainless steels (Febalance–18Cr–12Ni–1.5Mn–(0.19, 0.78, and 1.76 wt %)B) manufactured through conventional ingot metallurgy were investigated. The alloys were composed of an austenitic matrix and Cr2B phase, and the volume fraction of Cr2B increased from 1.68 to 22.66 vol % as the B content increased from 0.19 to 1.76 wt %. Potentiodynamic polarization tests measured in aqueous NaCl solutions revealed that the pitting corrosion resistance was reduced as the B content increased and the pits were initiated at the matrix adjacent to the Cr2B phase. It was found that the reduced resistance to pitting corrosion by B addition was due to the formation of more defective and thinner passive film and increased pit initiation sites in the matrix.